2012
DOI: 10.1089/pho.2012.3245
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Low-Level Laser Therapy in Reducing Pain Induced by Orthodontic Forces

Abstract: The significant reductions in both pain intensity and PGE(2) levels revealed that LLLT was efficient in reducing orthodontic post-adjustment pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 34 publications
4
68
0
6
Order By: Relevance
“…All articles included in this review have investigated laser analgesic action during some orthodontic treatment stage, be it placement of elastic separators [10][11][12] , in the adaptation of fixed appliances 1,2,7 or orthodontic tooth movement during adjustments 6,8 . These are recent studies published by relevant Orthodontics and Laser Therapy journals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All articles included in this review have investigated laser analgesic action during some orthodontic treatment stage, be it placement of elastic separators [10][11][12] , in the adaptation of fixed appliances 1,2,7 or orthodontic tooth movement during adjustments 6,8 . These are recent studies published by relevant Orthodontics and Laser Therapy journals.…”
Section: Discussionmentioning
confidence: 99%
“…Six drugs, they may have adverse effects on treatment; authors have also concluded that low intensity laser therapy is a relatively safe alternative needing further attention of the scientific community 4 . Recent studies have investigated the analgesic potential of Gallium-Aluminum-Arsenide (AsGaAl) laser under different protocols, during orthodontic treatment, and have shown promising results 2,[6][7][8] . Alternatives such as acupuncture and hypnosis have been indicated for some cases as pain therapy, being effective in some situations 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LLLT has been found to accelerate healing, stimulate nerve regeneration, increase fibroblastic and osteoblastic proliferation, decrease pain, and accelerate bone remodeling [8,13,14]. LLLT is a noninvasive therapy that uses low energy levels over long exposure periods.…”
Section: Introductionmentioning
confidence: 99%